(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The main challenge that faces management of valvular heart disease is that no medical therapies are known to decrease disease progression, or the resulting adverse outcomes on cardiac function. Cardiac imaging is essential to evaluate disease development and progression. It plays an important role in identifying valve lesion/dysfunction and to assess its severity as well as its impact on the cardiac function. Cardiac magnetic resonance (CMR) imaging may help in the assessment of Valvular heart disease. Our study was interested in studying Valvular lesions of different underlying pathologies and different forms of the resulting valve dysfunction (stenosis and/or regurgitation. The aim of this work was to assess role of cardiac MRI as a non-invasive tool in the evaluation of patients with Valvular heart disease in correlation with echocardiography. Methods: This prospective study included 40 patients suspected clinically and diagnosed by echocardiography with valvular heart disease. All patients were subjected to ECG monitoring, echocardiography and renal function test (blood urea, serum creatinine, estimation of glomerular filtration rate ‘eGFR’) and cardiac MRI examination. Results: There was fair agreement between echocardiography and CMR regarding the diagnosis of aortic regurgitation with kappa agreement coefficient (K = 0.242). There was perfect agreement between echocardiography and CMR regarding the grading of mitral stenosis with kappa coefficient (K = 0.813). There was moderate positive correlation between CMR-derived LV-EDV and MR volume as well as CMR-derived AR volume. Conclusions: Cardiac MRI added significant value to the assessment of valvular heart disease. It allows non-invasive, comprehensive evaluation of both valve lesion and its impact on the relevant cardiac chambers. It plays an important role in the assessment of patients with valvular affection with underlying congenital heart disease. CMR complements echocardiography and sometimes adds more additional valuable information.